Electric field induced spin resolved graphene p–n junctions on magnetic Janus VSeTe monolayer. (8th September 2022) - Hu, Yang; Ma, Yongjie; Ren, Weiwei; Pang, Rui; Hao, Dongfeng; Han, Xiaoyu; Wang, Fei; Cui, Bin; Li, Chong; Jia, Yu
Abstract: Graphene based p – n junctions exhibit intriguing and distinctive electronic properties, making them promising candidates for spintronic and spin photonic devices. While the attendant realization of magnetized graphene p – n junctions is highly desirable. Using first-principles calculations, we show that in the presence of magnetic proximity coupling effect of graphene supported on Te-termination magnetic Janus VSeTe monolayer (VSeTe/G), the graphene is readily spin-polarized and the Dirac bands near Fermi level keep intact. More interestingly, the external electric field ( E ex ) could significantly influence the bands of the spin down channel near Fermi level, due to the dominant electronic Coulomb screening effect. When the E ex exceeds 0.35 eV Å −1 with opposite direction to intrinsic dipole moment, the VSeTe/G heterostructure would turn into n type doping from the initial light p type doping in the spin down channel. However, those of the spin up channel in the vicinity of Fermi level are inert and still preserve initial p type against external electric field. In terms of such distinctive differences between the Dirac bands in the spin up and spin down channels, we propose a featured spin resolved graphene p – n junctions on magnetic Janus VSeTe by applying appropriate external electric field. Our findings are generally applicable to other similar magnetic Janus systems (i.e. graphene/FeICl) and might provide a feasible strategy to realize stable spin resolved graphene p – n junctions extendedly.